Study on the impact of China’s urban agglomerations’ tiered spatial structure on regional economic resilience - Wei Liang; Deqi Wang; Luqin Gao; Chunyan Li (PLoS ONE, 2025)
Urban agglomerations serve as crucial spatial carriers of economic development, and their spatial structure profoundly influences regional economic resilience. This study draws on Martin’s conceptualization of economic resilience and, considering the administrative hierarchy and development stage of China’s urban system, examines the impact of the layered spatial structure of urban agglomerations on regional economic resilience. Based on data from 17 Chinese urban agglomerations from 2005 to 2019, this research employs a one-step system Generalized Method of Moments (GMM) model to empirically analyze the effects of three mechanisms – polycentricity within urban agglomerations, inter-city development disparities, and inter-city industrial gradients – on regional economic resilience. The findings reveal that both the polycentric distribution of population and economy and the coupling of dual centers significantly positively affect the economic resilience of urban agglomerations. The potential development energy difference between core and peripheral cities can be transformed into developmental momentum for peripheral cities, thereby generating positive spatial externalities that play a significant and positive role in enhancing economic resilience. As the ratio of secondary to tertiary industry employees in peripheral and core cities nears 1, urban agglomerations’ economic resilience strengthens, underscoring the importance of a balanced industrial gradient and regional collaboration in mitigating economic shocks. This study also considers the heterogeneity of whether the urban agglomerations are coastal and whether they contain a national-level central city. The research finds that for inland urban agglomerations and those with existing national-level central cities, developing a polycentric spatial structure can effectively enhance the region’s economic resilience in responding to various shocks. Furthermore, aside from a few more developed coastal urban agglomerations, other inland urban agglomerations should continue to focus on spatial agglomeration, fostering core cities to strengthen economic competitiveness. Finally, given the varying industrialization stages and structures within urban agglomerations, appropriately adjusting the industrial gradient is essential.